Microbiota, metabolome, and immune alterations in obese mice fed a high‐fat diet containing type 2 resistant starch. Issue 11 (6th September 2017) - Barouei, Javad; Bendiks, Zach; Martinic, Alice; Mishchuk, Darya; Heeney, Dustin; Hsieh, Yu‐Hsin; Kieffer, Dorothy; Zaragoza, Jose; Martin, Roy; Slupsky, Carolyn; Marco, Maria L
Abstract : Scope: We examined the intestinal and systemic responses to incorporating a type 2 resistant starch (RS) into a high fat diet fed to obese mice. Methods and results: Diet‐induced obese, C57BL/6J male mice were fed an HF diet without or with 20% (by weight) high‐amylose maize resistant starch (HF‐RS) for 6 weeks. Serum adiponectin levels were higher with RS consumption, but there were no differences in weight gain and adiposity. With HF‐RS, the expression levels of ileal TLR2 and Reg3g and cecal occludin, TLR2, TLR4, NOD1 and NOD2 were induced; whereas colonic concentrations of the inflammatory cytokine IL‐17A declined. The intestinal, serum, liver, and urinary metabolomes were also altered. HF‐RS resulted in lower amino acid concentrations, including lower serum branched chain amino acids, and increased quantities of urinary di/trimethylamine, 3‐indoxylsulfate, and phenylacetylglycine. Corresponding to these changes were enrichments in Bacteroidetes (S24‐7 family) and certain Firmicutes taxa ( Lactobacillales and Erysipelotrichaceae ) with the HF‐RS diet. Parabacteroides and S24‐7 positively associated with cecal maltose concentrations. These taxa and Erysipelotrichaceae, Allobaculum, and Bifidobacterium were directly correlated with uremic metabolites. Conclusion: Consumption of RS modified the intestinal microbiota, stimulated intestinal immunity and endocrine‐responses, and modified systemic metabolomes in obese mice consuming an otherwise obesogenic diet. Abstract : Inclusion of type 2 resistant starch (RS) into high‐fat diet of obese mice induced alterations to hormonal and immune responses in the intestinal and adipose tissues. RS feeding also enhanced intestinal fermentation and altered gut microbiota and metabolomes in blood and liver including decreases in amino acids quantities. Glucose and maltose increased in the intestinal contents with RS consumption. Urinary metabolites differed between RS‐fed mice and control mice. These changes are mediated, at least partly, via alterations to the composition and function of gut microbiota.